Elderly with ischemic stroke: social-demographic and functional characterization - Chrystiany Plácido de Brito Vieira; Ana Virgínia de Melo Fialho; Paulo César de Almeida; Thereza Maria Magalhães Moreira (Rev Rene)
The objective was to describe the social-demographic and functional characteristics of elderly after ischemic stroke. Descriptive quantitative study carried out with a sample of accessibility of 52 elderly patients with ischemic stroke, in a health service in Fortaleza-CE-Brazil, between May and August 2009. We calculated the average and standard deviation for continuous variables and chi-square test to compare proportions in categorical variables. The results showed that 37 (71.2%) were between 60 and 79 years old, 43 (82.7%) lived in Fortaleza, 30 (57.7%) were married, with average family income of 2.5 minimum wages and 16 (30.8%) had a family history of the illness. The proportion of elderly was uniformly distributed in the range of disability and dependency (p=0.972 and p=0.780). The knowledge of the profile of the elderly is crucial because their quality of life has a strong connection with their social and economic reality, as well as with their functional capacity.